Analisis Kebijakan Manajemen Pesantren Di Indonesia - Alfina, Diya'; Muhammad, Muhammad (Jurnal Penelitian dan Pendidikan IPS, 2025)
Islamic boarding school education management is the key to improving the quality of education, building character, and adapting to the times. This study aims to evaluate Islamic boarding school management policies in Indonesia, with a focus on policy implementation and its impact on the development of Islamic boarding schools. The method used is a qualitative method with a literature review approach, and policy analysis. The results of the study show that government policies in managing Islamic boarding schools have experienced significant improvements, including through Law No. 18/2019, curriculum development, and operational assistance for Islamic boarding schools. However, there are several weaknesses in Islamic boarding school management, such as differences in the quality of education between Islamic boarding schools and limited development of general knowledge and technology. Therefore, it is important for Islamic boarding schools to continue to adapt to the development of the times without sacrificing traditional values, in order to produce a generation that is competent in the fields of religion and social life.